2017
DOI: 10.1111/jmi.12513
|View full text |Cite
|
Sign up to set email alerts
|

Precise observation of C. elegans dynamic behaviours under controlled thermal stimulus using a mobile phone–based microscope

Abstract: We investigated the temperature-dependent locomotion of Caenorhabditis elegans by using the mobile phone-based microscope. We developed the customized imaging system with mini incubator and smartphone to effectively control the thermal stimulation for precisely observing the temperature-dependent locomotory behaviours of C. elegans. Using the mobile phone-based microscope, we successfully followed the long-term progress of specimens of C. elegans in real time as they hatched and explored their temperature-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Its small size and ease of culture offer the ability to phenotype large populations offering statistical power, which can be a challenge with vertebrate models. Whole-organism phenotypic readouts in C. elegans typically involve examining animal behavior, locomotory prowess and survival in response to changes in environment [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its small size and ease of culture offer the ability to phenotype large populations offering statistical power, which can be a challenge with vertebrate models. Whole-organism phenotypic readouts in C. elegans typically involve examining animal behavior, locomotory prowess and survival in response to changes in environment [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The need to increase assay throughout and reduce costs has led to the development of a variety of bespoke imaging solutions. Approaches range from the use of scanners for parallel imaging of nematodes on agar plates [ 23 , 24 ] to compact do-it-yourself (DIY) systems based on Raspberry Pi cameras [ 25 , 26 , 27 ] and smartphones [ 10 , 28 , 29 ]. Scanners offer a convenient means to increase C. elegans assay throughout, but are bulky and generate heat that requires significant customization to maintain temperature during the assay [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These facets have limited the accessibility of the tool in resource‐limited regions (Breslauer et al ., ; Zhu et al ., ). Several research groups around the globe have recently been involved towards the development of a new platform using smartphone which can be reliably used for sensing of different physical and chemical parameters (Gallegos et al ., ; Lopez‐Ruiz et al ., ; Dutta et al ., ; Dutta et al ., ; Hossain et al ., ; Hussain et al ., ; Dutta et al ., ; Hussain et al ., ,b; Mutlu et al ., ; Chen et al ., ; Natesan et al ., ) and imaging of various biological samples (Vashist et al ., ; Knowlton et al ., ; Contreras‐Naranjo et al ., ; Scherr et al ., ; Yoon et al ., ; Sun & Hu, ; Jawale et al ., ; Purwar et al ., ). Currently, there are approximately 8.1 billion mobile phone subscribers around the world, and ∼40% of the phone subscribers use smartphones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have also shown the ability of mobile microscopes to capture static features of the cell, nucleus as well as single DNA molecules [2, 57]. Further it has also been used to measure the dynamic features of the cell such as its motility [8]. These methods have opened new avenues for mobile microscopes to be used as tools for clinical diagnostics to assess different types of human samples.…”
Section: Introductionmentioning
confidence: 99%